Incidence of fungi on yellow passion fruit seeds in the Maranhão State (Brazil) - Catunda, Paulo Henrique Aragão; Silva, Edvan Costa da; Costa, Maria Aline da Silva (Scientia Agraria Paranaensis, 2021)
In recent years, passion fruit orchards have suffered from the high incidence of microorganisms, causing damage from the seedling phase to the post-harvest of the fruits; among these microorganisms are the fungi that comprise the largest number of species associated with the seeds. The objective of this work was to evaluate the incidence of fungi associated with yellow passion fruit seeds in the State of Maranhão. The experiment was carried out in 2014 and conducted at the Seed Laboratory of the State University of Southern Maranhão (UEMASUL), Campus Imperatriz. Fruit seeds collected from six municipalities in the state of Maranhão (Carolina, Capinzal do Norte, Estreito, Imperatriz, Vila Nova dos Martírios and São Luís) were used. A completely randomized design with four replications was adopted. A total of 400 seeds were used per municipality, 50 per gerbox, totaling the processing and analysis of 2400 seeds in general. The incidence of pathogenic agents in the seeds was determined by using the filter paper method with freezing, using four replications of 100 seeds per evaluated municipality. Seven days later, the incidence of pathogens was estimated by using a stereomicroscope, with confirmation of the genus and/or species of the fungus. The incidence of Penicillium sp. in yellow passion fruit seeds occurred in all assessed municipalities collected. The city of Vila Nova dos Martírios has presented the highest incidence of fungi, while the city of Imperatriz has had the lowest rate.